2018
DOI: 10.1007/s11356-018-1341-7
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non-linear impact of Internet usage and financial deepening on electricity consumption for Turkey: empirical evidence from asymmetric causality

Abstract: This study investigates the relationship between Internet usage, financial development, economic growth, capital and electricity consumption using quarterly data from 1993Q1 to 2014Q4. The integration order of the series is analysed using the structural break unit root test. The ARDL bounds test for cointegration in addition to the Bayer-Hanck (2013) combined cointegration test is applied to analyse the existence of cointegration among the variables. The study found strong evidence of a long-run relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…In an attempt to increase the sample size and the accuracy of the empirical results in the asymmetric causality testing, this study follows the works of Faisal et al (2018), Shahbaz et al (2017), and Sbia et al (2014) by adopting quarterly frequency data from 1981Q1 to 2016Q4. Quadratic match-sum approach is employed to transform annual frequency data to quarterly frequency data.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to increase the sample size and the accuracy of the empirical results in the asymmetric causality testing, this study follows the works of Faisal et al (2018), Shahbaz et al (2017), and Sbia et al (2014) by adopting quarterly frequency data from 1981Q1 to 2016Q4. Quadratic match-sum approach is employed to transform annual frequency data to quarterly frequency data.…”
Section: Methodsmentioning
confidence: 99%
“…In this connection, Faisal, Tursoy, and Berk (2018a) conducted a study to analyse the linear and non-linear relationship between financial development and Internet usage for Turkey. The study utilised the ARDL bounds testing approach to identify the evidence of cointegration.…”
Section: Finance-growth Nexusmentioning
confidence: 99%
“…eir results showed that improving energy efficiency equipment and mobile communication equipment for Internet Protocol (IP) communications were the most effective measures to reduce electricity demand. With quarterly data from 1993q1 to 2014q4, Faisal et al [15] used the ARDL approach to confirm that there was a U-shaped relationship between Internet use and EC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, some achievements have confirmed the demand growth effect of ITC on EC [10][11][12][13][14][15][16]. Unfortunately, the existing empirical literature on the relationship between ICT and EC does not consider the spatial dependence of EC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation